THE FORMATION AND DEVELOPMENT OF HISTORICAL AND NATIONAL CHARACTERISTICS IN LITERARY TRANSLATION - Hamroyeva Sharifa Shukur qizi (Western European Studies, 2025)
The issue of restoring national characteristics and historicity remain highly relevant both theoretically and practically in contemporary translation studies. Addressing this challenge in the translation process requires a creative approach, the effective utilization of lexical and semantic resources, and the preservation of the overall aesthetic essence of the original work. These factors play a crucial role in ensuring the accuracy and authenticity of the translated text.
Keywords: translation; historical text; transformation